Konstruksi Pemberitaan Tragedi Kanjuruhan (Analisis Framing Di Detik.Com) - Duku, Sumaina; Kurnia, Kurnia; Yahya, Ahmad Harun (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This research is entitled "Construction of Reporting on the Kanjuruhan Tragedy (Framing Analysis at Detik.com)." The background of this research is because the Kanjuruhan Tragedy is one of the major events in the history of Indonesian football which resulted in many victims and hundreds of victims died. The purpose discussed in this study is to find out how to analyze framing and news construction related to the Kanjuruhan tragedy in the online media Detik.com. This study used qualitative research methods. The theory used in this study is the Zhongdang and Pan Kisocki framing theory using 4 framing tools, namely, syntax, script, thematic and rhetorical. Based on the results of the research by analyzing 8 news stories, it was found that regarding the reporting on the Kanjuruhan tragedy, the Detik.com media tried to be objective by positioning themselves as a neutral party and applying the principle of balance. However, in several news stories, Detik.com tries to sway public opinion. This can be seen from the several frames built into the news text.